The Archetypal Analysis on Main Characters of Stephen King's Rita Hayworth and Shawshank Redemption - Thesalonika Alvina; Mike Wijaya Saragih (Prodi Sastra Inggris UKI, 2023)
This research article explores the application of Jungian archetypal theory in analyzing Stephen King's novella, Rita Hayworth and Shawshank Redemption. The primary focus of this analysis is to uncover the archetypal identities embodied by the central characters, Andy Dufresne and Ellis